Prevalence of Depression, Anxiety, Stress, and Quality of Life among Individuals with Hemodialysis: Hemodialysis and Quality of Life - Haider, Ali Saqlain; Unbrin, Aqila; Shahzadi, Mafia (Pakistan Journal of Health Sciences, 2024)
Hemodialysis was filtering the blood of a person whose kidneys were not working normally. Objective: To investigate the prevalence of depression, anxiety, stress, and quality of life among individuals with hemodialysis. Methods: A total of 134 patients were taken from the hospitals of Lahore. The participant’s age ranges were between 20-60 years. A purposive sampling technique was used to collect the data. The following measures were used to assess the findings i.e., Demographic, Depression Anxiety Stress Scale (DASS), and World Health Organization Quality of Life Brief (WHOQOL). Results: The analyses revealed that the high prevalence of depression, anxiety, and stress in hemodialysis patients and significantly poor quality of life in hemodialysis patients. Conclusion: It was concluded that hemodialysis, the most common treatment for end stage renal disease, was a risk factor for psychological illnesses such as depression and anxiety. So, there was a need to develop a treatment strategy, including therapeutic invitations that eventually, improve quality of life.